P PENGARUH MODEL THINK PAIR SHARE (TPS) BERBASIS MEDIA GAMBAR TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SEKOLAH DASAR : PENGARUH MODEL THINK PAIR SHARE (TPS) BERBASIS MEDIA GAMBAR TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SEKOLAH DASAR - Nurvela Resti; Silvester (Program Studi Tadris IPA IAIN Parepare, 2026)
Abstract: This study aims to determine the effect of the Think Pair Share (TPS) learning model based on image media on the science learning outcomes of fifth-grade elementary school students. This study used a quantitative approach with a pre-experimental design in the form of a One Group Pretest-Posttest Design. The research subjects were 23 fifth-grade students at SD Negeri 10 Tiga Desa. Data collection techniques included tests, observation, and documentation. Data analysis was conducted through a swimmer test (normality and homogeneity) and hypothesis testing using a paired sample t-test. The results showed that the average pretest score of 46.52 increased to 81.47 in the posttest. The results of the hypothesis test showed a significance value <0.05, indicating a significant effect. Thus, the TPS learning model based on image media is effective in improving students' science learning outcomes. Keywords: Think Pair Share, image media, learning outcomes, science.